Voices of exile in contemporary Canadian francophone literature - Dahab, Elizabeth (After the empire., 2009)
Over the last four decades, the largest French-speaking state in North America, QuZbec, has nested more than a dozen vibrant modes of French expression created by members of the varied cultural communities that have settled there. Voices of Exile in Contemporary Canadian Francophone Literature examines the works of several first-generation Canadian authors originating from Lebanon, Iraq, Egypt, and the Maghreb, who produced a trilingual literature that reflects the diversity of their cultural backgrounds. By casting a critical eye on the works of Saad Elkhadem, Naim Kattan, Abla Farhoud, Wajdi.